2016
DOI: 10.1186/s12915-016-0337-3
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of influenza H3N2 intra-subtype reassortment: attributes and implications of reassortant spread

Abstract: BackgroundIncreasing evidence suggests that influenza reassortment not only contributes to the emergence of new human pandemics but also plays an important role in seasonal influenza epidemics, disease severity, evolution, and vaccine efficacy. We studied this process within 2091 H3N2 full genomes utilizing a combination of the latest reassortment detection tools and more conventional phylogenetic analyses.ResultsWe found that the amount of H3N2 intra-subtype reassortment depended on the number of sampled geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 71 publications
2
23
0
Order By: Relevance
“…With eight gene segments, the chance that a coinfected individual transmits a new reassortant strain would be much higher, at nearly 100 per cent, such that around 5 per cent of the infected population would be expected to carry a first-generation reassortant virus. Interestingly, this low-level reassortment is consistent with an estimated frequency of reassortment events observed among sampled virus genomes over time, at around 3.35 per cent ( Maljkovic Berry et al 2016 ). This observation, in part, could be explained by the likelihood of coinfection, and thus reassortment, being reduced as result of herd immunity—that is viral infections with novel antigenic variants are less likely to occur in individuals that have been previously infected with older antigenic variants.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…With eight gene segments, the chance that a coinfected individual transmits a new reassortant strain would be much higher, at nearly 100 per cent, such that around 5 per cent of the infected population would be expected to carry a first-generation reassortant virus. Interestingly, this low-level reassortment is consistent with an estimated frequency of reassortment events observed among sampled virus genomes over time, at around 3.35 per cent ( Maljkovic Berry et al 2016 ). This observation, in part, could be explained by the likelihood of coinfection, and thus reassortment, being reduced as result of herd immunity—that is viral infections with novel antigenic variants are less likely to occur in individuals that have been previously infected with older antigenic variants.…”
Section: Discussionsupporting
confidence: 85%
“…selective sweeps and genetic bottlenecks) will also similarly impact the rest of the virus genome. However, whole-genome analyses of seasonal influenza A viruses indicate that reassortment is relatively frequent, with each gene segment having somewhat of a distinctive evolutionary history ( Holmes et al 2005 ; Nelson et al 2008b ; Rambaut et al 2008 ; Westgeest et al 2014 ; Maljkovic Berry et al 2016 ). Estimated differences in the times to most recent common ancestor (TMRCA) across the genome can also exceed 6 years ( Rambaut et al 2008 ), which is inconsistent with strong linkage effects solely shaping the genetic diversity patterns of this virus.…”
Section: Introductionmentioning
confidence: 99%
“…However, important examples include the appearance of H1N2 viruses detected sporadically in humans (Guo et al 1992;Xu et al 2002;Ellis et al 2003;Al Faress et al 2008). In contrast, intra-subtype reassortment occurs frequently (Holmes et al 2005;Nelson et al 2008;Rambaut et al 2008;Westgeest et al 2014;Berry et al 2016) and likely far more so than detected through phylogenetic analysis as it may involve parental lineages that are difficult to distinguish on evolutionary trees and/or the inclusion of internal gene segments often not included in analyses.…”
Section: Ecology and Evolution Of Influenza Virusesmentioning
confidence: 99%
“…There are limited data on reassortment during human infection, though one study has suggested that the effective reassortment rate may be relatively low during acute infection (62). At the host population level however, reassortment appears common among circulating seasonal IAVs of the same subtype and may have played a role in increasing the severity of some seasonal epidemics (63)(64)(65)(66)(67)(68).…”
Section: Reassortmentmentioning
confidence: 99%